PERILAKU KELUARGA TENTANG PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI TATANAN RUMAH TANGGA BERDASARKAN JENIS PERUMAHAN DI RT 02 DAN 04 KELURAHAN BUKIT KAYU KAPUR KECAMATAN BUKIT KAPUR - Puspaini, Ririn (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
One of the goals of Indonesia's health development in 2025 is to increase awareness, willingness and ability to live a healthy life for everyone through the creation of an Indonesian society, nation and state characterized by its population living in a healthy environment. So the Republic of Indonesia Ministry of Health developed Guidelines for the Promotion of Clean and Healthy Behavior in the household system, namely empowerment in the household structure for individuals, families and community groups. Achievement of Clean and Healthy Behavior in Bukit Kapur District in 2019 by 50% which is not in accordance with the Ministry of Health Strategic Plan (Renstra) target for 2010-2014 of 70%. The purpose of this study was to determine the description of family behavior about Clean and Healthy Behavior in household settings based on the type of housing in RT 02 and RT 04 kelur hill kayu kelur hill kapur sub-district. The research design is descriptive. Non random sampling with purposive sampling, the number of samples is 60 families. The study was conducted from June 6 to June 13, 2019. The results of the study of family behavior of luxury housing type indicators of the use of clean water with positive behavior of 12 families (60%) and negative 6 families (30%), medium housing type indicators of washing hands with clean water and soap and eradicate larvae at home with positive behavior of 12 families (60%) and negative 6 families (30%), a type of simple housing indicator not smoking inside the house with positive family behavior (25%) and negative by 15 families (75% ). Researchers hope that all parties cooperate with each other in the distribution of health information and the community will further improve health information and conduct clean and healthy living